2019
DOI: 10.1136/bmjgh-2018-001078
|View full text |Cite
|
Sign up to set email alerts
|

Quality gap in maternal and newborn healthcare: a cross-sectional study in Myanmar

Abstract: IntroductionAccess to maternal and newborn healthcare has improved in Myanmar. However, regular contact with skilled care providers does not necessarily result in quality care. We assessed adequate contact made by women and newborns with skilled care providers, reception of high-quality care and quality-adjusted contacts during antenatal care (ANC), peripartum care (PPC) and postnatal care (PNC) in Myanmar.MethodsThis cross-sectional study was conducted in a predominantly urban township of Yangon and a predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 36 publications
3
28
0
1
Order By: Relevance
“…Socioeconomic inequality in ANC contacts exists in Myanmar, as it does in almost all countries around the world. 24 28 39 40 In this study, pregnant women in the lower socioeconomic strata were at a higher risk for not initiating ANC early, not receiving the recommended number of ANC contacts or receiving adequate ANC components. We demonstrated that Myanmar could achieve ~51% coverage of up to seven ANC contacts, if all women were in the highest wealth quintile households.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Socioeconomic inequality in ANC contacts exists in Myanmar, as it does in almost all countries around the world. 24 28 39 40 In this study, pregnant women in the lower socioeconomic strata were at a higher risk for not initiating ANC early, not receiving the recommended number of ANC contacts or receiving adequate ANC components. We demonstrated that Myanmar could achieve ~51% coverage of up to seven ANC contacts, if all women were in the highest wealth quintile households.…”
Section: Discussionmentioning
confidence: 78%
“…18 Previous research investigating ANC in Myanmar has identified factors associated with utilisation and access to care during pregnancy, 19–21 birth and postbirth 22 23 and highlighted the need to improve the quality of maternal and newborn care services. 24 However, these studies did not investigate the new WHO recommended ANC guidelines. In 2018, the Myanmar Ministry of Health and Sports issued a national guideline for ANC based on the 2016 WHO guideline for delivery of ANC services.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons behind this might be not enough in understanding or early diagnosis of the severity of the problems, perceived distance of hospital and cost as demonstrated in other study in Nepal. 20 Besides, traditional practices and the status of women can play important roles in the first delay. The main decision makers in household are men in this study.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Besides, there could be a deficiency in high-quality antenatal care and counselling as has been observed in a study in Myanmar. 20 The in-depth understanding of the severity of risk and early communication, especially by the pregnant women herself is important. A study in India reported major cause in first delay was due to caregiver unawareness of severity of problem.…”
Section: Discussionmentioning
confidence: 99%
“…For instance a bottleneck analysis for newborn survival identified wide gaps in almost all aspects of the implementation of intervention packages aimed at in-patient care of the small and sick newborns [7]. In rural populations in Pakistan, despite improved access to primary healthcare services, the quality of care still lags behind best practice [8]. Although the main risk factors [9] and interventions to prevent perinatal mortality have been identified [10], there still exist gaps in our understanding of how these interventions are integrated within community-based maternal and child healthcare services in countries with a high burden of perinatal mortality.…”
Section: Introductionmentioning
confidence: 99%